Molecular Genetics of Breast and Ovarian Cancer: Recent Advances and Clinical Implications - Dörk Thilo; Bogdanova N (Balkan Journal of Medical Genetics, 2012)
Over the last few years, evidence has been accumulated that several susceptibility genes exist that differentially impact on the lifetime risk for breast or ovarian cancer. High-to-moderate penetrance alleles have been identified in genes involved in DNA double-strand break signaling and repair, and many low-penetrance susceptibility loci have been identified through genome-wide association studies. In this review, we briefly summarize present knowledge about breast and ovarian cancer susceptibility genes and discuss their implications for risk prediction and therapy.